The effect of Remin Pro on the microhardness of initial enamel lesions in primary teeth: An in vitro study - Homa Nourolahian; Iman Parisay; Fatemeh Mir (Wolters Kluwer Medknow Publications, 2021)
Background: Remineralization is currently considered a treatment option for many clinicians. The present study was conducted to compare the effect of three remineralizing agents on microhardness of initial caries lesions in primary teeth. Materials and Methods: In this in vitro study, 96 enamel samples were prepared. Microhardness was first measured for all the samples using the Vickers microhardness test. After developing the initial caries lesions, the microhardness of all the demineralized samples was measured, and the samples were then divided into four groups (n = 24). Casein phosphopeptide-amorphous calcium phosphate in Group 1, Remin Pro in Group 2, and acidulated phosphate fluoride gel in Group 3 were placed on the samples for 4 min. The control group received no treatments. The microhardness of the samples was measured again following a pH cycle of 5 days. The data were analyzed by ANOVA and the post hoc test at the significance level of P < 0.05. Results: The mean microhardness reduced significantly in all the groups following the development of initial caries lesions and after the pH cycle of 3 days (P < 0.001). After the remineralization and pH cycle of 5 days, the mean microhardness was significantly lower in the control group compared to the other three groups (P < 0.001) and had increased in the three treated groups. The microhardness recovery rate also increased in the treated groups compared to the control group, but no significant differences were observed between the three groups themselves (P > 0.05). Conclusion: Remin Pro can be used as an effective substance for preventing tooth caries in children.